India's Mental Healthcare Act, 2017 Evaluation of the Act, its Context and Initial Implementation - Duffy, Richard Michael (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2022)
The United Nations has initiated a paradigmatic shift in mental healthcare through the United Nations Convention on the Rights of Persons with Disabilities (CRPD), in addition to this the WHO has identified legislation as a key tool for improving healthcare. In 2016, India adopted the Rights of Persons with Disabilities Act (RPWDA), closely followed in 2017 by the Mental Healthcare Act (MHCA). These Acts are pioneering pieces of legislation, both were explicitly written to bring Indian legislation in line with the CRPD. This research evaluated the concordance of India s Mental Health legislation with international standards and explored the views of psychiatrists in India. To examine this, a black letter analysis was conducted comparing the RPWDA and the MHCA with the CRPD and the World Health Organization s Checklist on Mental Health Legislation from the WHO Resource Book (WHO-RB). Thirteen focus groups were conducted and included 93 mental health professionals, in 4 Indian states, over a two-year period. This was done to compliment and inform the blackletter analysis. In depth thematic analysis was also carried out on data in relation to two key topics: electroconvulsive therapy and assisted decision making. Themes and sub-themes relating to these topics were identified and discussed. The black letter analysis highlighted a number of areas of non-concordance in the Indian legislation and identified the complexities of simultaneously protecting competing rights. Many potentially non-concordant areas stemmed from the interpretation of the Committee on the Rights of Persons with Disabilities rather than the text of the CRPD itself. The focus groups revealed that the concerns of psychiatrists were often divergent or at odds with the international standards. They also highlighted that resource limitation and cultural differences will need to be overcome to adequately implement the new legislation. The complexity of using international standards and conventions as a mechanism for realising human rights for individuals with mental health problems was discussed.
APPROVED
Keywords: Mental Health Legislation; CRPD; WHO; Mental Healthcare Act, 2017; Medical Ethics